ANALISIS PENGENDALIAN INTERNAL PERSEDIAAN BARANG DAGANG PADA PT PASAR BUAH 88 - Monica Tannusa; Hamdani Arifulsyah; Atika Zarefar (Politeknik Caltex Riau, 2018)
The purpose of this research is to know the comparison between the internal control of merchandise inventory at PT Pasar Buah 88 with the COSO-based internal controlling standard (COSO). The method used in analyzing this research is qualitative method. Data collection techniques are interview techniques and questionnaires. Based on the results of the research, the internal control of merchandise inventory at PT Pasar Buah 88 amounted to 39.86% which means less effective, because the company has not fully implemented the five components of COSO. The results of this study indicate that internal controls in PT Pasar Buah 88 are less effective with COSO inventory control standards. Keywords : Internal Control, Merchandise Inventory, COSO (Committee of Sponsoring Organizations of the Treadway Commission).